2021
DOI: 10.21203/rs.3.rs-858163/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A rapid real-time polymerase chain reaction-based live virus microneutralization assay for detection of neutralizing antibodies against SARS-CoV-2 in blood/serum

Abstract: Background Individuals recovering from COVID-19 are shown to have antibodies against the Spike and other structural proteins. Antibodies against Spike have been shown to display viral neutralization. However, not all antibodies against Spike have neutralizing ability and some may be cross-reactive. There is a need for easy-to-use SARS-CoV-2 neutralizing assays that allow the determination of virus neutralizing activity in sera of individuals. Here we describe a PCR-based micro-neutralization assay that can be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…IgG to RBD is associated with neutralizing activity (45) (46). We found IgG to RBD measured in both COVID-19 convalescent and healthy individuals to be associated with neutralizing activity to SARS-CoV-2 (47). Aijaz et al reported from Pakistan that antibodies to RBD after BBIBP-CorV vaccination were associated with neutralizing antibodies (29).…”
Section: Discussionmentioning
confidence: 85%
“…IgG to RBD is associated with neutralizing activity (45) (46). We found IgG to RBD measured in both COVID-19 convalescent and healthy individuals to be associated with neutralizing activity to SARS-CoV-2 (47). Aijaz et al reported from Pakistan that antibodies to RBD after BBIBP-CorV vaccination were associated with neutralizing antibodies (29).…”
Section: Discussionmentioning
confidence: 85%
“…Alternatively, recombinant SARS-CoV-2 virus expressing Green Fluorescent Protein can be detected directly without the need for further processing (25). Another approach is to detect viral genetic material in cell lysates through RT-qPCR following RNA extraction (26, 27) or to quantify replicating virus (viral load) by enzyme-linked immunosorbent assay (ELISA) (28). Other assays score the presence or absence of CPE under a microscope (29, 30) using a cell imager (31), or using colorimetric cellular dyes (29).…”
Section: Introductionmentioning
confidence: 99%